PERFORMANCE ANALYSIS OF A RAILWAY LEVEL CROSSING UNDER MIXED TRAFFIC CONDITIONS IN BEKASI REGENCY, INDONESIA. - Alfian Darmawan; Sri Nuryati; Elma Yulius; Ninik Paryati; Eko Darma; Fajar Prihesnanto; Anita Setyowati Srie Gunarti (Journal of Sustainable Civil Engineering (JOSCE), 2026)
This study contributes an integrated evaluation approach combining traffic performance analysis and user perception to support evidence-based decision making for the management and upgrading of railway level crossing under mixed traffic conditions